Beyond sounds and words volume in honour of Janina Aniela Ozga - Niżegorodcew, Anna; Jodłowiec, Maria (Jagiellonian University Press, 2011)
The present volume is a token of gratitude for our colleague, Janina Aniela Ozga, a senior lecturer at the Institute of English Philology of the Jagiellonian University. The book is a collection of papers on a wide spectrum of topics, ranging from Hamlet to Zoolander, which reflect diverse academic interests of the authors: literary theory, linguistics, translation studies, philosophy of language, history and language teaching. The common thread running through all the papers is the desire of the authors - all of them humanists involved in academic pursuits - to place in a theoretical perspective of their discipline and shed new light on an interesting research problem in literature, art, language use or language teaching that they have identified
Title from publisher's bibliographic system (viewed on 31 May 2016)
Keywords: Ozga, Janina / 1946-; Linguistik; Philosophie; Sprache; Language and languages / Philosophy; Linguistics